Virtual leadership adaptation in times of crisis: a process framework from a South African higher education institution - Badru, Abdulbaqi; Gerwel Proches, Cecile; Mulaudzi, Christinah (Frontiers in Education, 2026)
IntroductionThe COVID-19 crisis served as a disruptive catalyst for reimagining leadership in higher education institutions (HEIs), particularly within resource-constrained and traditionally contact-based environments. This disruption demanded rapid adaptation from leaders who were unprepared for the abrupt transition to virtual work. The study focused on understanding how academic leaders and directors of professional services within a traditional South African HEI navigated this transformation in leadership practice during the national shutdown.MethodsA qualitative research design was adopted, employing semi-structured interviews with academic and administrative leaders. The data were analysed thematically to capture patterns and dimensions of adaptive leadership behavior. Nicholson’s (2013) Adaptive Cycle Model was used as a guiding framework to interpret how leaders’ experiences aligned with the cyclical interplay between situational context, leadership processes, and adaptive qualities.ResultsThree overarching dimensions of leadership adaptation emerged from the data: situational challenges, adaptive processes, and enabling qualities. Leaders encountered multiple contextual challenges, including institutional and structural barriers, team disengagement, and personal strain. Despite these difficulties, participants demonstrated progressive adaptation through a three-phase transition process, Discovery, Normalisation, and Stability, marking a developmental shift from uncertainty and experimentation toward competence and confidence in virtual leadership. Enabling factors such as institutional support, collaboration, flexibility, and digital competence facilitated this transformation.DiscussionThe findings reveal that leadership adaptation during crisis conditions is a cyclical and developmental process rather than a linear progression. The study underscores the dual necessity of organisational preparedness and individual agility in navigating disruptive change. By integrating challenges, transition phases, and enablers within Nicholson’s (2013) Adaptive Cycle Model, the study proposes a holistic framework for understanding adaptive virtual leadership in higher education. This framework contributes to emerging scholarship by highlighting the need for resilient, digitally literate, and future-oriented leadership within increasingly hybrid academic contexts.